DIMENSI SYIFA' (PENYEMBUHAN) DALAM AL-QURAN DAN KHASIAT GURAKA SEBAGAI MINUMAN TRADISIONAL MALUKU UTARA - tawang, Salehuddin Mattawang; Sulaeman; Dardirie, Achmad; Amri, Muhammad; Saefuddin, A'raf (LPPM IAIN Sultan Amai Gorontalo, 2025)
This study examines the dimension of syifa' (healing) in the Quran and its relevance to the properties of Guraka as a traditional beverage of North Maluku. The Quran mentions the concept of syifa' in six verses, which scholars understand as holistic healing encompassing spiritual, psychological, and physical dimensions. This qualitative research employs the tafsir maudhui (thematic exegesis) method combined with an ethnographic approach, with primary data sources consisting of classical commentaries (al-Thabari, Ibn Katsir, al-Qurthubi, al-Razi) and contemporary ones (Sayyid Quthb, Hamka, M. Quraish Shihab, Wahbah al-Zuhaili), as well as field data from North Maluku. The findings reveal: (1) the concept of syifa' in the Quran is holistic and integrative in nature; (2) Guraka has a strong pharmacological basis, with bioactive compounds proven to possess analgesic, antioxidant, and anti-inflammatory effects; (3) there exists a theological coherence between Quranic syifa' and the Guraka tradition, which integrates al-dawa' (herbal medicine), al-du'a' (prayer), and al-tawakkul (complete reliance upon Allah). This study proposes the paradigm of